Pengaruh Struktur Kepemilikan dan Kualitas Audit terhadap Manajemen Laba - Elisa Putri Agustin; Jacobus widiatmoko (Politeknik Ganesha Medan, 2022)
Earnings management influenced by company’s ownership structure and audit quality. This study was made with the aim of empirically proving the effect of ownership structure (managerial ownership, institusional ownership, foreign ownership, and ownership concentration), and audit quality on earnings management, with the addition of profitability and leverage variables as control variables. This study uses quantitative research methods with secondary data collection techniques. The sample collection method in this study used a purposive sampling method with specified criteria. Secondary data for the study was taken from the annual report of manufacturing companies listed on the Indonesia Stock Exchange with the research year 2017 to 2020. The source of secondary data in this study was obtained through www.idx.co.id. This research sample counted 141 companies that meet criteria. Data processing using SPSS application. The analysis technique used is multiple linear regression analysis. Based on the results of the tests and research that have been described, it is concluded that there is a significant negative effect between the variables of institutional ownership, ownership concentration and audit quality on earnings management. Managerial ownership and foreign ownership variables have no significant effect on earnings management. Of the two control variables used in this study, only leverage has a negative effect on earnings management, while profitability does not affect earnings management. The R-Squared value of 52% can be explained by the variables contained in this study, while the remaining 48% is influenced by factors not explained in this study.